Forecasting the number of cerebrovascular patients in Lopburi Province - Jayathavaj, Vadhana; Toonsakul, Patchara (Journal of Medical and Public Health Region 4, 2025)
From fiscal year 2014 to 2023, Lopburi Province's number of stroke patients doubled from 1,528 to 3,020. Forecasting the number of patients in fiscal years 2024 and 2025 using a time series model will be basic administrative information, and the model can be improved for further forecasting. Because there are only 12 years of statistical data on the number of stroke patients in Lopburi Province (fiscal years 2013–2024, processed on January 12, 2024), the linear regression method was chosen. and Gray System Theory, GM (1,1) model. The result of the linear regression equation method has a mean absolute error percentage (Mean Average Percentage Error, MAPE) of 2.9, giving a forecast value for the number of patients in fiscal years 2024 and 2025 equal to 3,180 and 3,337 people, respectively. As for the GM(1,1)-I model, when using data from fiscal years 2013 to 2023 with the GM(1,1)-II model using data from fiscal years 2013 to 2023, it has a MAPE of 3.71 and 4.45, respectively, which are within the criteria for good forecasting. The GM (1,1)-I model has the number of patients in fiscal year 2024 equal to 3,368 people. The GM (1,1)-II model gives a forecast value of the number of patients in fiscal years 2024 and 2025 equal to 3,253 and 3,475 people, respectively. The GM(1) model,1)-II provides a forecast that is in the middle between the linear regression method and the GM(1,1)-I model and should therefore be used as the forecast.